COVID-19–associated central nervous system mucormycosis - Anjali Mishra; Dinesh Mohan Chaudhari; Pushpendra Nath Renjen (Apollo Medicine)
Mucormycosis is a life-threatening infection caused by fungi of the order Mucorales. Central nervous system (CNS) mucormycosis is usually an extension of the infection from the sinuses to the eyes and brain. CNS mucormycosis arises from an adjacent paranasal sinus infection (rhinocerebral) by direct extension or hematogenous dissemination from the lungs, but isolated CNS mucormycosis is a rare presentation. During an episode of fungemia, seeding may occur in brain tissue, leading to this infection. The most common clinical presentation of mucormycosis is rhino-orbital-cerebral infection, which is presumed to start with inhalation of spores into the paranasal sinuses of a susceptible host. In this article, we emphasize on the COVID-19–associated mucormycosis, particularly the involvement of CNS.